2020
DOI: 10.26434/chemrxiv.12434174.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simultaneous Inhibition of Entry and Replication of Novel Corona Virus by Grazoprevir: A Computational Drug Repurposing Study

Abstract: <div> <div> <div> <p>It is evident from the on-going clinical studies (trials) for coronavirus disease 2019 (COVID-19) that treatment with a single drug is not likely to be sufficient. This, in turn, suggests that the drug acts via inhibition of multiple pathways likely to be more successful and promising. Keeping this hypothesis intact, the present study describes for the first-time, Grazoprevir, an FDA approved anti-viral drug primarily approved for HCV, mediated multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Grazoprevir inhibited SARS-CoV-2 with an EC50 around 16 µM (CC50 value >100 µM). Published computational studies suggested grazoprevir as a potential inhibitor of the nucleocapsid protein or the papain-like protease of SARS-CoV-2 (Behera et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Grazoprevir inhibited SARS-CoV-2 with an EC50 around 16 µM (CC50 value >100 µM). Published computational studies suggested grazoprevir as a potential inhibitor of the nucleocapsid protein or the papain-like protease of SARS-CoV-2 (Behera et al, 2020).…”
Section: Discussionmentioning
confidence: 99%